The Effect of Rolling Massage on Breast Milk Production in Breastfeeding Mothers at Tidore City Hospital - Lisnawati Husen; Anik Sri Purwanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Breast milk is the optimal source of nutrition for infants, and adequate milk production is essential to support infant growth and development. However, many breastfeeding mothers experience difficulties in milk production, particularly during the early postpartum period. Rolling massage is a non-pharmacological intervention that is believed to stimulate the release of oxytocin and prolactin hormones, thereby enhancing breast milk production. This study aimed to determine the effect of rolling massage on breast milk production in breastfeeding mothers at Tidore City Hospital.This research employed a pre-experimental design with a one-group pretest–posttest approach. A total of 30 breastfeeding mothers were selected as the sample using purposive sampling techniques. Breast milk production was assessed before and after the implementation of rolling massage. The intervention was performed according to standardized procedures. Data were analyzed using the Wilcoxon signed-rank test to evaluate differences in breast milk production before and after the intervention.The results showed a significant increase in breast milk production after the rolling massage intervention. Statistical analysis using the Wilcoxon signed-rank test revealed a p-value of 0.000 (p < 0.05), indicating a significant effect of rolling massage on breast milk production in breastfeeding mothers.In conclusion, rolling massage has a significant positive effect on increasing breast milk production among breastfeeding mothers. This intervention can be recommended as a simple, safe, and effective complementary therapy to support successful breastfeeding, particularly in the early postpartum period.